BIBLIOMETRIC INVESTIGATION: UNCOVERING FINANCIAL INCLUSION AND FINANCIAL PERFORMANCE OF SMES - Yogantara, Komang; Yadnyana, I Ketut; Sudana, I Putu; Sujana, I Ketut (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
SMEs face various challenges that hinder the improvement of their financial performance. Access to finance is the most perceived barrier. This study aims to review the literature and dissect the current utilization of financial inclusion, with a focus on SMEs, especially their financial performance. This review synthesizes previous literature to identify institutions and journals that lead publications, theories, and approaches used. Through a bibliometric investigation, a search indexed in Scopus and Science Direct resulted in the acceptance of 45 peer-reviewed papers published from 2019 to April 2024. This review identifies several methodological gaps in the literature that have the potential for further research. This study also reveals that financial inclusion is often a challenge, especially for SMEs in improving their financial performance. The identified mediating roles may provide implications for SMEs to align financial inclusion with the goal of better financial performance.